Students' willingness to Communicate in Extramural English Activities in Digital EFL Context: A Narrative Inquiry - Dinda Malyndra; Nur Arifah Drajati; Muhammad Asrori (EDULANGUE, 2020)
The changing of offline language learning into online language learning as a new way to learn English resulted in students’ engagement in social media activities. This research tries to investigate the effects of social media activities towards students’ willingness to communicate. The researcher interviewed 4 EFL students form one state university in Indonesia. All participants are active social media users who have learnt English for about 10 years, and they have experienced international internship for their teaching practicum. The result of this research yielded that engaging in social media helped the students improve their English ability, learn new culture form other countries, and accept the diversity of English. This result validated the existing views regarding the topic of IDLE and WTC. This research may help future researchers that the result of this research presents a narrative avenue for future L2 WTC studies, and enables future researchers to consider digital EFL contexts when conducting L2 WTC research.